Asymptotic behavior of the products of random matrices with values on a solvable Lie algebra - Chani, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The index of exponential growth is found for the products of random matrices with values on a solvable Lie algebra. The result is expressed via the eigenvalues of the terms.